THE EFFECT OF IMPLEMENTING A COOPERATIVE LEARNING MODEL OF GROUP INVESTIGATION (GI) TYPE ON STUDENT LEARNING OUTCOMES ON ECOSYSTEM MATERIALS IN CLASS XA OF STATE MIDDLE SCHOOL 2 SINTANG - Marzuki, Marzuki (LPPM Institut Pendidikan Nusantara Global, 2023)
This study analyzed the effect of implementing the group investigation (gi) cooperative learning model on student learning outcomes on ecosystem material in class XA of SMA Negeri 2 Sintang. The researcher used a qualitative method to conduct the study. Thirty-four student samples from Class X A were taken using purposive sampling. The learning model implementation was going well and proven from the observation sheet; 84.62% of teachers and 88.89% of students were in the